On the Nusselt Solution of a Nonisothermal Two-Fluid Inclined Film Flow - Jürgen Socolowsky (International Journal of Mathematics and Mathematical Sciences)
Nonisothermal viscous two-fluid flows occur in numerous kinds of coating devices. The corresponding mathematical models often represent two-dimensional free boundary value problems for the Navier-Stokes equations or their modifications. In the present paper we are concerned with a particular problem of coupled heat and mass transfer. Marangoni convection is incorporated, too. The solvability of a corresponding stationary problem is discussed. The obtained results generalize previous results for a similar isothermal problem.